Effects of the Pd3Co Nanoparticles-Additive on the Redox Shuttle Reaction in Rechargeable Li-S Batteries. Issue 10 (1st January 2016) - Yom, Jee Ho; Cho, Sung Man; Hwang, Sun Woo; Yoon, Woo Young
Abstract : A lithium-sulfur (Li-S) battery system with bimetallic electrode additive, which limit the dissolution of intermediate lithium polysulfides, is studied. Palladium-cobalt (Pd3 Co) nanoparticles are successfully employed as redox promoters in Li-S cells. These cells show high capacity retention and excellent Coulombic efficiency, which are attributed to the fast charge transfer of Pd3 Co. Characterization of the Pd3 Co nanoparticles is performed via high-resolution transmission electron microscopy, fast Fourier transform analysis, energy-dispersive X-ray, and X-ray diffraction. At 0.1 C-rate, the initial discharge and charge capacities of the Pd3 Co-sulfur electrodes are 1.24 and 1.36 times higher than those of the bare sulfur electrodes. During the first discharge cycle, the overpotential of the Pd3 Co electrode (100 mV) is much lower than that of the bare sulfur cell (190 mV). After 200 cycles at 1.0 C-rate, the Pd3 Co-sulfur electrodes deliver a discharge capacity of 544 mAh g −1 and a high Coulombic efficiency (99.6%). Moreover, the capacity retention of Pd3 Co cells is 83.9%. The inductively coupled plasma-atomic emission spectroscopy and X-ray photoelectron spectroscopy data demonstrate that the Pd3 Co nanoparticles can suppress the dissolution of lithium polysulfides and the shuttle effect. These results indicate that the reaction kinetics of the sulfur electrodes is enhanced by the Pd3 Co nanoparticles.